Information Systems Foundations: Theory, Representation and Reality - Hart, Dennis; Gregor, Shirley (Information Systems Foundations, 2007)
This volume contains the papers presented at the third biennial Information Systems Foundations ('Theory, Representation and Reality') Workshop, held at The Australian National University in Canberra from 27-28 September 2006. The focus of the workshop was, as for the others in the series, the foundations of Information Systems as an academic discipline. The particular emphasis was, as in past workshops, the adequacy and completeness of theoretical underpinnings and the research methods employed. At the same time the practical nature of the applications and phenomena with which the discipline deals were kept firmly in view. Accordingly, the papers in this volume range from the unashamedly theoretical n their focus (Designing for Mutability in Information Systems Artifacts; Towards a Unified Theory of Fit: Task, Technology and Individual) to the much more practically oriented (An Action-Centred Approach to Conceptualising Information Support for Routine Work). The contents of this volume will be of interest and relevance to academics and advanced students as well as thoughtful and reflective practitioners in the Information Systems field.